A Critical Evaluation of English Test in Government-affiliated College - Monalisa Pasaribu (Linguists : Journal Of Linguistics and Language Teaching, 2019)
This study aims at evaluating an English test as part of entrance test in STAN, a government-affiliated college in Indonesia. STAN EPT has four main sections in the test including Structure and Written Expression, Cloze Question, Error Recognition and Reading Comprehension. Using five criteria by Brown & Abeywickrama (2010), the test is evaluated in terms of its practicality, reliability, validity, washback and authenticity. The result indicated that the test has high practicability with all of questions provided in multiple choices. Some elements of reliability and validity are also covered in this test. Yet, the evaluation also showed that washback and authenticity are not covered in STAN EPT. Key words: STAN EPT, English test, test evaluation